THE STUDENTS’ PERCEPTION ON THE ADVANTAGES OF GROUP DISCUSSION TECHNIQUE IN TEACHING SPEAKING AT THE ELEVENTH GRADE IN SMAN 1 VII KOTO SUNGAI SARIK - Fikrina, Aulia; Arifmiboy, Arifmiboy; Reflinda, Reflinda; Roza, Veni (Universitas Pendidikan Ganesha, 2021)
This research was due to some problems that were found at 11th grade of SMAN 1 VII Koto. First, some students said that they think the group discussion was good for them to improve their speaking skill. However, there were still some students who do not like group discussion since it makes the classroom become noisy and lost their focus in learning. Then, tends to focus on the students who can ask and answer questions in English correctly. Meanwhile, the students who are shy and cannot speak English fluently do not get enough attention in the class. Second, the researcher found that some students do not really cooperate in the group discussion. The reseacher used descriptive quantitative reseach to describe the phenomena of students’ perception on the advantages of group discussion technique in teaching speaking. The population of this research was all the students at eleventh grade in SMAN I VII KOTO SUNGAI SARIK. The sample of this research was 38 students that was chosen randomly. Then, 20 items questionnaire was used as the instrument of the research. This research used closed questionnaire in which the respondent has to choose/check one or more responses of the presented variants ofanswering. Based on the results of the study, students' perceptions on the advantages of group discussion techniques in teaching speaking in eleventh grade at SMAN 1 VII Koto Sungai Sarik found that 32.28% of respondents strongly agreed that the benefits of discussion could improve understanding, critical thinking, personal growth, communication skills, self-direction in learning. While 59.76% of respondents agreed, 6.73% of respondents were neutral, 1.13% of respondents did not agree, and 0% of respondents strongly disagreed.